The Dietary Approaches to Stop Hypertension Diet, Cognitive Function, and Cognitive Decline in American Older Women - Berendsen, Agnes A M; Kang, Jae H; van de Rest, Ondine; Feskens, Edith J M; de Groot, Lisette C P G M; Grodstein, Francine (Journal of the American Medical Directors Association, 2017)
To examine the association between long-term adherence to the Dietary Approaches to Stop Hypertension (DASH) diet with cognitive function and decline in older American women. Prospective cohort study. The Nurses' Health Study, a cohort of registered nurses residing in 11 US states. A total of 16,144 women from the Nurses' Health Study, aged ≥70 years, who underwent cognitive testing a total of 4 times by telephone from 1995 to 2001 (baseline), with multiple dietary assessments between 1984 and the first cognitive examination. DASH adherence for each individual was based on scoring of intakes of 9 nutrient or food components. Long-term DASH adherence was calculated as the average DASH adherence score from up to 5 repeated measures of diet. Primary outcomes were cognitive function calculated as the average scores of the 4 repeated measures, as well as cognitive change of the Telephone Interview for Cognitive Status score and composite scores of global cognition and verbal memory. Greater adherence to long-term DASH score was associated with better average cognitive function, irrespective of apolipoprotein E ε4 allele status [multivariable-adjusted differences in mean z-scores between extreme DASH quintiles = 0.04 (95% confidence interval, CI 0.01-0.07), P trend = .009 for global cognition; 0.04 (95% CI 0.01-0.07), P trend = .002 for verbal memory and 0.16 (95% CI 0.03-0.29), and P trend = .03 for Telephone Interview for Cognitive Status, P interaction >0.24]. These differences were equivalent to being 1 year younger in age. Adherence to the DASH score was not associated with change in cognitive function over 6 years. Our findings in the largest cohort on dietary patterns and cognitive function to date indicate that long-term adherence to the DASH diet is important to maintain cognitive function at older ages.